The Choice between Corporate and Structured Financing: Evidence from New Corporate Borrowings - Pinto, João Monteiro (2021)
We examine the factors that influence nonfinancial firms’ choice of issuing standard corporate bonds vis-à-vis contracting structured finance transactions, in the form of project finance or asset securitization deals. Using a data set of deals closed by 4,700 European borrowers between 2000 and 2016, we find that informational and agency problems, and issuance costs, affect public firms’ borrowing source choices. Findings also suggest that firms choose structured finance borrowings when they are less profitable and have lower asset tangibility. Our findings document that transaction cost considerations lead firms that use both structured finance and corporate bond deals during our sampling period, to choose structured finance for new borrowings. Additionally, firms resorting to project finance are less creditworthy than corporate bond issuers are and, on average, asset securitization deals have a funding cost advantage of 87.6 basis points over corporate bond deals.